Does Digital Financial Inclusion Impact ESG Performance in Islamic and Conventional Financial Institutions? A Global Evidence - M. Kabir Hassan; Mustafa Raza Rabbani; Madiha Kiran (Bank Indonesia, 2025)
This study investigates the impact of digital financial inclusion on corporate ESG performance using a global sample of 660 conventional and Islamic institutions from 2010 to 2022. The study reveals that digital financial inclusion can significantly promote corporate ESG performance. What sets this study apart is its use of the novel methodology of fixed effects model and Methods of Moments Quantile Regression (MMQR) to empirically identify how digital financial inclusion affects corporate ESG performance from lower to higher quantiles (0.1 to 0.9). Further, the analysis using 1st and 2nd SLS shows that digital financial inclusion has a more pronounced impact on Islamic banks' ESG scores, mainly when involved in the high implementation of digitalization. These significant results are assured by legitimacy and stakeholder theories. ESG factors have been significantly affected by adopting modern digital applications and platforms in regulated industries of Islamic institutions. Sub-Sample analysis of financial institutions and heterogeneity analysis of more and less board independence and board size significantly impact implementing digital financial inclusion and ESG performance, instilling the need to mitigate banks' risks by disclosing non-financial information and resolving agency conflicts among stakeholders aimed at investing in sustainable green projects. Finally, our results remain robust after addressing endogeneity issues and conducting robustness checks, offering new insights into the evolving digital financial inclusion and ESG performance.